2014
DOI: 10.1071/en13227
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the photo-oxidative and heterogeneous chemical production of HCHO in the snowpack at the South Pole, Antarctica

Abstract: Environmental context. Snowpacks present a surprisingly active environment for photochemistry, leading to sunlight-induced oxidation of deposited organic matter and the subsequent emission of a variety of photochemically active trace gases. We seek to address questions regarding the ultimate fate of organic matter deposited onto snow in the remote regions of the world. The work is relevant to atmospheric composition and climate change.Abstract. We investigate snowpack fluxes of formaldehyde (HCHO) into the Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For example, Hamer et al modeled photochemical production of formaldehyde in a snowpack from a variety of different sources, and concluded that CH 3 OOH photolysis is a relatively minor source of formaldehyde. 254 …”
Section: Heterogeneous Photochemistry At Ice Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hamer et al modeled photochemical production of formaldehyde in a snowpack from a variety of different sources, and concluded that CH 3 OOH photolysis is a relatively minor source of formaldehyde. 254 …”
Section: Heterogeneous Photochemistry At Ice Surfacesmentioning
confidence: 99%
“…Despite the theoretical interest in CH 3 OOH, its ice photochemistry may be too slow to affect the polar environments. For example, Hamer et al modeled photochemical production of formaldehyde in a snowpack from a variety of different sources, and concluded that CH 3 OOH photolysis is a relatively minor source of formaldehyde …”
Section: Heterogeneous Photochemistry At Ice Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have observed significant changes in the concentration of gases contained in the deposited snow due to metamorphism, photolysis, diffusion out of the snow crystals, etc. [104]- [106] In addition, the distribution of impurities between the different domains of the condensed phase inside the snowpack (at the grain surface, in the bulk of the solid, in liquid trapped in confined pockets between grains), the presence of a multiphase system where liquid solutions and ice coexist, and changes in snow structure and properties affect both physical processes and Snow-grain metamorphism ATMOSPHERE chemical reactivity [107].…”
Section: The Post-depositional Processmentioning
confidence: 99%